Reliability of the tunisian pediatric gait, arms, legs, and spine: toward a valid screening tool for tunisian children with musculoskeletal conditions - Lassoued Ferjani Hanene; Narjess Amdouni; Rabhi Emna; Sahli Hela; Ben Abdelgheni Kaouther; Ben Nessib Dorra; Kaffel Dhia; Maatallah Kaouther; Hamdi Wafa (BMC, 2023)
Abstract Background Pediatric musculoskeletal disorders account for 10% of first-line consultations in Tunisia. Referral delay and deficiencies in musculoskeletal screening raise a challenge to the early diagnosis and management of rheumatic conditions in children. The pGALS (Pediatric Gait Arms Legs Spine) was developed and translated into many languages to overcome these deficiencies. Our study aimed to adapt and validate pGALS to the Tunisian dialect for school-age children. Methods Using the Delphi method, we carried out a cross-cultural adaptation of the pGALS to the Tunisian dialect. This consensual version was validated in a cross-sectional study, in two pediatric centers. Results Ninety-two patients were enrolled, 43 females (46.7%) and 49 males (53.3%), mean age was 9.4 ± 2.6 years. The mean test duration was 3.4 ± 2.3 min, and the acceptability and comprehension of the test were good. Six patients had a musculoskeletal complaint, 19 had positive pGALS, and 14 were diagnosed with musculoskeletal disease. The internal consistency score (Cronbach's α) was 0.852. The sensitivity of the test was 92.8%, the specificity was 92.3%, the positive likelihood ratio was 2.16, and the negative likelihood ratio was 0.01. Conclusion The pGALS test adapted to the Tunisian dialect is a relevant, quick, and valid tool for screening musculoskeletal abnormalities in school-age children.